2018
DOI: 10.1093/intqhc/mzx170
|View full text |Cite
|
Sign up to set email alerts
|

Patient perspectives on how physicians communicate diagnostic uncertainty: An experimental vignette study†

Abstract: Parents may react less negatively in terms of perceived competence, physician confidence and trust, and intention to adhere when diagnostic uncertainty is communicated using implicit strategies, such as using broad differential diagnoses or most likely diagnoses. Evidence-based strategies to communicate diagnostic uncertainty to patients need further development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
77
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(79 citation statements)
references
References 46 publications
0
77
1
1
Order By: Relevance
“…Patients' understanding of uncertainties reduces misconceptions about prognosis and increases adherence to treatment. The way ambiguity is presented to the patient matters: In a study using different strategies of communication, implicit expression of uncertainty (using a broad differential diagnosis) improved patient's confidence as compared with explicit expression of uncertainty …”
Section: Empathy As a Key Tool To Handle Uncertaintymentioning
confidence: 99%
See 1 more Smart Citation
“…Patients' understanding of uncertainties reduces misconceptions about prognosis and increases adherence to treatment. The way ambiguity is presented to the patient matters: In a study using different strategies of communication, implicit expression of uncertainty (using a broad differential diagnosis) improved patient's confidence as compared with explicit expression of uncertainty …”
Section: Empathy As a Key Tool To Handle Uncertaintymentioning
confidence: 99%
“…The way ambiguity is presented to the patient matters: In a study using different strategies of communication, implicit expression of uncertainty (using a broad differential diagnosis) improved patient's confidence as compared with explicit expression of uncertainty. 53 Humanism entails an empathic, respectful, and open-minded communication, but also concerns the contents of the conversation.…”
Section: Empathy As a Key Tool To Handle Uncertaintymentioning
confidence: 99%
“…It also showed that physicians did not seek out resources when they most needed them in midst of difficult cases when they were likely to be most uncertain. Communication of diagnostic uncertainty among patients and clinicians has also been found to be challenging . A recent Institute of Medicine report “ Improving Diagnosis in Health Care ” has called for efforts to improve diagnostic decision‐making through better measurement .…”
Section: Discussionmentioning
confidence: 99%
“…3 Despite this, doctors may be hesitant to express their diagnostic indecision to patients, and frequently find themselves relying on 'self-made' techniques to do so, such as using qualifying words like 'possibly' or 'maybe' . 3,4 As well as the generally poor outcomes that patients report following consultations where clinical uncertainty is expressed by their doctor, this hesitancy indicates the need for a commonly taught and evidencebased approach to holding such conversations. 4 In order to address this gap in medical education, communication skills sessions with actors playing patients who are not acutely ill may enable senior students to practise discussing clinical uncertainties.…”
mentioning
confidence: 99%
“…3,4 As well as the generally poor outcomes that patients report following consultations where clinical uncertainty is expressed by their doctor, this hesitancy indicates the need for a commonly taught and evidencebased approach to holding such conversations. 4 In order to address this gap in medical education, communication skills sessions with actors playing patients who are not acutely ill may enable senior students to practise discussing clinical uncertainties. In summary, we should welcome the introduction of more opportunities for students to learn about dealing with clinical uncertainty, but in doing so educators must ensure that the patient as a whole is considered.…”
mentioning
confidence: 99%